Congenital cataract - Zmelonek-Znamirowska, Anna; Wolder, Daniel; Komar-Gruszka, Karolina; Gruszka, Jakub; Zwierzyńska, Anna; Adamczyk-Gruszka, Olga (Journal of Education, Health and Sport, 2021)
Cataract is an eye disease that means opacification of the lens of the eye leading to partial or total blindness. It is common and treatable cause of blindness in children [1]. The prevalence of cataract in children worldwide ranges from 1 to 15 per 10,000. In developed countries, the incidence is 1 to 3 per 10,000 [2]. Cataracts can be detected using a prenatal ultrasound scan performed between 18 and 20 weeks of pregnancy [3,4,5]. Early detection of cataracts and rapid intervention are crucial in the development of normal vision, especially in newborns [4]. The article presents a case report of intrauterine ultrasonographic diagnosis of congenital cataract.